On Identities in Algebras $Q_{n,λ}$ Generated by Idempotents - Rabanovych, V. I.; Samoilenko, Yu. S.; Strilets, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the presence of polynomial identities in the algebras $Q_{n,λ}$ generated by $n$ idempotents with the sum $λe$ ($λ ∈ C$ and $e$ is the identity of an algebra). We prove that $Q_{4,2}$ is an algebra with the standard polynomial identity $F_4$, whereas the algebras $Q_{4,2},\; λ ≠ 2$, and $Q_{n,λ},\; n ≥ 5$, do not have polynomial identities.